2006
DOI: 10.1007/s00726-005-0282-x
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in taurine levels induced by β-alanine treatment did not affect the susceptibility of tissues to lipid peroxidation

Abstract: We aimed to investigate the effect of decreased taurine levels on endogenous and induced lipid peroxide levels in liver, brain, heart and erythrocytes as well as prooxidant and antioxidant balance in the liver of rats administered beta-alanine (3%, w/v) in drinking water for 1 month to decrease taurine levels of tissues. This treatment caused significant decreases in taurine levels of liver (86%), brain (36%) and heart (15%). We found that endogenous and ascorbic acid-, NADPH- and cumene hydroperoxide-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…According to this, the balance between prooxidant and antioxidant systems seems to be highly sensitive to taurine depletion in the heart tissue of old rats. On the contrary, in our recent study, although the administration of 3% ␤-alanine in the drinking water of young rats decreased taurine levels in the heart (15%), this treatment was found not to alter endogenous, AA-or NADPH-induced lipid peroxidation in heart homogenates (38).…”
Section: Discussioncontrasting
confidence: 70%
“…According to this, the balance between prooxidant and antioxidant systems seems to be highly sensitive to taurine depletion in the heart tissue of old rats. On the contrary, in our recent study, although the administration of 3% ␤-alanine in the drinking water of young rats decreased taurine levels in the heart (15%), this treatment was found not to alter endogenous, AA-or NADPH-induced lipid peroxidation in heart homogenates (38).…”
Section: Discussioncontrasting
confidence: 70%
“…b-alanine is a competitive inhibitor of taurine to the taurine transporter activity. 1 Previous studies have shown that b-alanine treatment administered in the drinking water at a concentration of 3% causes a decline in taurine plasma levels [34][35][36] and in tissues such as the hippocampus, posterior cortex, and retina, as well as in cellular taurine content 13,14,[37][38][39][40] and also that taurine depletion causes loss of retinal neurons 6,41-43 (see below). [50][51][52] Light is a risk factor for some retinal degenerations, [53][54][55][56] and it accelerates photoreceptor degeneration in some inherited retinal degenerations.…”
Section: Discussionmentioning
confidence: 99%
“…TauT mediates the uptake of taurine from the extracellular space into the cell, thus maintaining high intracellular levels of taurine. To examine the pathophysiological role of taurine, models of taurine deficiency were developed by knocking out the TauT gene, nutritional depletion, an inhibitor of taurine intake, such as guanidinoethane sulfonate, or β‐alanine, and carbon tetrachloride (CCL 4 ), which time‐dependently significantly decreases taurine (86%) in the liver . Mitochondrial taurine content decreased by 60% after supplementation with β‐alanine .…”
Section: Models Of Taurine Deficiencymentioning
confidence: 99%